2018
DOI: 10.1080/13683500.2018.1444020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of local food in sustaining Chinese destinations

Abstract: Food is a sustainable part of destination tourism. However, few studies attempt to separate and examine the role played by local foods within tourists' overall experience when claiming the benefits that local foods can bring to a destination.Using Mainland China as the case in point, this study aims to evaluate the potential for destinations to use local food as a sustainable marketing tool. This is achieved through examining how local food, as part of the tourist experience, can contribute to tourists' destin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 71 publications
(101 reference statements)
1
45
0
1
Order By: Relevance
“…The favorable response of tourists to their food experiences forms revisit intentions to a destination. This is supported by the research studies of Chen and Chen (2010), Meleddu et al (2015), and Chen and Huang (2019).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The favorable response of tourists to their food experiences forms revisit intentions to a destination. This is supported by the research studies of Chen and Chen (2010), Meleddu et al (2015), and Chen and Huang (2019).…”
Section: Discussionmentioning
confidence: 70%
“…This is true with the studies of Laurent and Kapferer (1985), Prayag and Ryan (2012) and Lee and Chang (2012) who identified that when tourists are very much involved in a destination, it positively affects their degree of satisfaction and loyalty. On the other hand, Chen and Huang (2019) observed that local food involvement does not affect loyalty to a destination. Additionally, the study also revealed that food satisfaction directly affects destination loyalty.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations